Hungernomics: explaining food trade sustainability - Evan, Lau; SNZ, Hamzah; SA, Sallih; MA, Arip (Faculty of Food Science and Technology, 2013)
This study explores the relationship between the total exports and total imports of the food industry in Sarawak from 1961 through 2007. We examined the sample period of the pre-1997 crisis (1961-1996) and the full sample period (1961-2007) to investigate disparities for pre- crisis sample. Analysis was carried out using standard econometric procedure and Dynamic OLS estimation for the annual observations of the two sample period. This study’s major findings are: (1) long run relationships were detected in the full sample period whereas they were absent in the pre-crisis period; (2) imbalances in food were found to be weakly sustainable for the full sample; (3) for every ringgit increase in imports, exports rose by RM0.803 for the full sample, revealing that imports grew at a rate faster than exports. This finding suggests that reducing the size of imports may improve imbalances in Sarawak’s food industry.